Improvement of relationship between main contractor and subcontractor for successful construction project implementation - Lagiman, Syahidah (2017)
Cooperation between the main contractor and subcontractor to deliver the construction project within the time, quality and cost are important in the construction industry. The success of the construction project depends on the subcontractors because they are the party that execute the technical and the operation of the works. The main contractor needs to possess the ability to effectively coordinate and manages the sub-contractors. Despite to this importance, there are relationship issues between the main contractor and the subcontractor that required to be reviewed. The objectives of this research were to determine the factors leading to relationship problems between the main contractors and subcontractors in a construction project and to propose recommendations to improve the main contractor and subcontractor relationship for a successful project implementation. A qualitative method was chosen and face to face semi-structure interview was conducted by having the discussion with six respondents from both main contractors and subcontractors. The scope of this research is the housing development project in Johor Bahru. The data collected was analysed using content analysis. The outcome of this research concluded the relatives to this issues, the factors leading to relationship problems between the main contractor and subcontractor are time and cost overrun factor, delay, trust, lack of quality, lack of communication, lack of safety, shortage of construction material and shortage of skill labors. On the other hand, the recommendation to improve the relationship between both parties are skill, integrity, trust, responsibility and communication application which is mutual in a contractual relationship between both parties. In conclusion, the finding can assist in the improvement of the main contractor and subcontractor relationship for successful construction project implementation.